Sosialisasi Dampak Sampah Terhadap Kesehatan dan Demonstrasi Pembuatan Spray Anti Nyamuk - Ellen D. Oktanti Irianto; Jumi Auliya; Masyadit Aditia; Nanda Putri Ramadhani; Noor Cahaya Ningrum; Muhammad Divka Akmal Nugroho; Dinda Eka Safira; Nasywa Salsabila; Nurul Aisyah; Rista Maulidawati; Yonggi Wijaya (Jurnal Ragam Pengabdian, 2025)
Waste management remains one of the major challenges affecting public health in many developing regions, including Samboja Kuala Village, Kutai Kartanegara District. Improperly managed household waste often serves as a breeding ground for Aedes aegypti, the vector of dengue hemorrhagic fever (DHF), which continues to cause high morbidity in Indonesia. This community service program aimed to increase public awareness of the health impacts of waste and to provide practical skills in producing a natural mosquito repellent spray using lemongrass (Cymbopogon citratus) and orange peels. The program was carried out through several stages, including preparation, socialization using lectures and educational media (leaflets and posters), demonstration of the production process, and mentoring. Thirty community participants and ten KKN students were involved in the activity. The evaluation employed pre-test and post-test questionnaires to measure knowledge improvement. The results indicated a significant increase in participants’ average scores, from 22.73 in the pre-test to 29.36 in the post-test. Furthermore, participants successfully produced a natural mosquito repellent spray that was safe, environmentally friendly, and easy to apply. These outcomes demonstrate that combining education with hands-on practice is effective in improving knowledge and skills while promoting environmentally friendly solutions that utilize organic waste. The program is expected to raise collective awareness of environmental health and has the potential to be sustained as a local innovation with economic value.